Analysis of Antifungal Resistance Genes in Candida albicans Isolates Using Next Generation Sequencing - Maha M. Mohammed; Azhar A. F. Al-Attraqchi; Dalal S. Alrubaye (Iraqi Journal of Medical Sciences, 2025)
Background:Candida albicans (C. albicans) is determined as the major human pathogen in the genus Candida. The presence of virulence genes and the increasing prevalence of resistance to antifungal therapy have contributed to the pathogenicity of C. albicans. Next-generation sequencing (NGS), also known as high-throughput sequencing, is the catch-all term used to describe a number of different modern sequencing technologies. These technologies allow for sequencing of DNA and RNA much more quickly and cheaply than the previously used Sanger sequencing, and as such revolutionized the study of genomics and molecular biology. Objective: To determine the mutations in the genes responsible for multidrug resistance among isolates of pathogenic C. albicans using NGS technique. Methods: This study comprises a total of (1596) samples collected from different body sites and lesions (blood, wounds swabs, ear swabs, bronchoalveolar lavage, high vaginal swabs, sputum, threat swabs, and urine); after diagnosis the C. albicans isolates DNA extraction was done and final using NGS technique. Results: Only 209 of 1596 samples that were taken from the patients and cultured on Sabouraud\'s dextrose agar were found to be positive. Candida isolates were cultured on Chrom Candida Agar the results revealed that 59 of the isolates were C. albicans. ERG11 gene in this study found to cause 12 silent mutations, while missense mutation was just two compared with reference sequences standard strains SC5314. ERG11 gene in this study found to cause 12 silent mutations, while missense mutation was just two. One deletion mutation was found in the YOR1 gene in this investigation, this gene alone has 2 silent mutations and 1 missense mutation, the PDR16 gene contained 15 missense mutations and 6 silent mutations. Conclusion: This study showed that next generation sequencing allows the thorough investigation of isolates more cost efficient and faster than another technique. Keywords: Candida albicans, NGS technique. Citation: Mohammed MM, Al-Attraqchi AAF, Alrubaye DS. Analysis of antifungal resistance genes in Candida albicans isolates using next generation sequencing. Iraqi JMS. 2025; 23(1): 46-57. doi: 10.22578/IJMS.23.1.6